The relative age effect and the relationship between biological maturity and athletic performance in Austrian elite youth soccer players - Mirko Wenger; Mirko Wenger; Robert Csapo (Frontiers in Sports and Active Living)
PurposePublications from recent years suggest that the biological developmental stage of underage athletes has a significant impact on their athletic performance. This scientific study is the first quantitative attempt in Austria to investigate the impact of the relative age effect and biological maturity on the physical performance of young elite soccer players.MethodsBirth data from a total of 98 male players in the U13 to U18 age groups of a first-division Austrian soccer club were collected. By measuring height, sitting height and body mass, the individual biological age was calculated using the Mirwald equation. The athletes underwent a standardized battery of tests, which included assessments of speed, strength and endurance.ResultsThe results indicate a significant effect of the relative age effect on player selection in the U14 and U15 teams (p < .05), which diminishes with increasing player age. Compared to typical Austrian adolescents of similar age, U13, U14 and U15 players demonstrate a higher level of biological maturity (p < .05). Correlational analyses revealed that the maturity offset, reflecting the time before or after the greatest individual growth spurt, was positively related to eccentric hamstring strength (r = 0.82) and vertical jumping ability (r = 0.61) and positively related to sprint performance over 5, 10 and 20 m (0.62 < r < 0.69; all p ≤ .001).ConclusionBiological maturity and the associated anthropometric adaptations are decisive for athletic performance. The study supports the notion that biologically more mature players achieve better athletic performance than less mature players, especially before the onset of puberty.